Celiac disease 2015 update: new therapies. (September 2015) - Veeraraghavan, Gopal; Leffler, Daniel A; Kaswala, Dharmesh H; Mukherjee, Rupa
<x xml:space="preserve">Abstract</x> Celiac disease (CD) is a chronic, small intestinal, immune-mediated enteropathy triggered by exposure to dietary gluten in genetically susceptible individuals. Currently, lifelong adherence to a gluten-free diet (GFD) is the only available treatment. However, GFD alone is not sufficient to relieve symptoms, control small intestinal inflammation and prevent long-term complications in many patients. The GFD has its challenges including issues related to adherence, lifestyle restrictions and cost. As a result, there is growing interest in and a need for non-dietary therapies to manage this condition. In recent years, different targets in the immune-mediated cascade of CD have been identified in clinical and pre-clinical trials for potential therapies. This review will discuss the latest non-dietary therapies in CD, including endopeptidases, modulators of enterocyte tight junctions and agents involved in gluten tolerization and immunomodulation. We will also discuss the potential implications of approved therapeutics on CD clinical practice.